Enhancing Vocational Students' English Proficiency: The Impact of Role-Play Method - Efrizah, Doni; Fadly, Yossy; Putri, Vivi Oxana (Proceeding International Conference on Malay Identity, 2024)
Speaking English is an essential skill for vocational high school students to succeed in the world of work. However, many students face challenges such as limited vocabulary, low self-confidence, and minimal practice opportunities. This study examines the effect of the role-play method on improving English-speaking skills among students at SMK SPP SNAKMA. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation involving 35 tenth-grade students. Results reveal significant improvements in students' speaking abilities. Specifically, 85% of participants demonstrated increased confidence, 70% expanded their active vocabulary, and over 60% achieved better pronunciation and contextual communication skills. These findings underscore the role of active, situational learning in fostering practical English communication. The study highlights role-play as a transformative method for equipping vocational students with industry-relevant speaking skills.